Development and validation of a LC-ESI-MS method for detection of piperidin-1-ium {[5-(2-furyl)-4-phenyl-4H- 1,2,4-triazol-3-yl] thio}acetate residues in poultry eggs - Varynskyi, B. O.; Parchenko, V. V.; Kaplaushenko, A. G.; Panasenko, O. I.; Knysh, Ye.; Варинський, Борис Олександрович; Парченко, Володимир Володимирович; Каплаушенко, Андрій Григорович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович (My University, 2016)
A simple, rapid and reproducible isocratic reversed-phase LC-ESI-MS method has been elaborated for determination of the piperidin-1-ium {[5-(2-furyl)-4-phenyl-4H-1,2,4-triazol-3-yl] thio}acetate, active pharmaceutical ingredient (API) of the antiviral veterinary drug “Tryfuzol” in the poultry eggs. The samples were extracted by dimethyl sulfoxide at ultrasonic bath, centrifuged at 15000 g, filtrated through ultrafilter and injected into HPLC system. A mobile phase was used 0.1% (v/v) formic acid in water (A) and acetonitrile containing 0.1% (v/v) formic acid (B) at isocratic elution. The composition of the mobile phase was A/B (70%:30%, v/v) at flow rate of 0.4 ml min-1. Total running time was 5 minutes. Mass spectrometric conditions were SIM mode (m/z 302.1), positive polarity. The mean concentration were 0.2887-7.204% of the nominal values for the QC samples. The within-run CV values were 1.564-5.636% for the QC samples. The method is applicable for determination of the residual quantities of API of the “Tryfuzol” in the poultry eggs.
Keywords: ESI mass spectrometry; high pressure liquid chromatography; poultry eggs; triazoles; tryfuzol